Isolasi dan Uji Aktivitas Antioksidan Ekstrak Metanol Dari Buah Senduduk Bulu (Clidemia hirta (L.) D. Don) - Fadhli, Haiyul; Ikhtiarudin, Ihsan; Lestari, Putri (Pharmacon: Jurnal Farmasi Indonesia, 2020)
A study on isolation and antioxidant activity of secondary metabolit of methanol extract of fruit of Senduduk Bulu (Clidemia hirta (L.) D. Don) has been carried out. Senduduk bulu is used for folk medicine to many diseases. Flavonoid and phenolic has been reported to its activity as antioxidant. The aim of this research was to find antioxidant compound and antioxidant activity of this fruit. Isolation works were conducted using Vacuum Liquid Chromatography and Column Chromatography method. Antioxidant activity was determined using DPPH free radical scavenging methods. The isolation works afforded 10 mg of pure compound CHP1 which was obtained as white crystal, with its melting point of 165–167ºC, soluble in chloroform and slightly soluble in methanol. This compound gave positive reaction with Liebermann-Burchard (LB) reagent and concluded as terpenoid. Based on it UV spectrum, this compound showed a λ max of 316 nm. Its FT-IR spectrum showed appearence of some functional groups of OH, C-H aliphatic, C=O ester,C=C alkene, CH bending and C-O. The 1H-NMR spectrum showed the alkene protons and methyl protons which is a characteristic of terpenoid compounds. The pure compound (CHP1) provided a weak antioxidant activity with the IC50  of 327,01µg/mL.